1997
DOI: 10.1006/viro.1997.8635
|View full text |Cite
|
Sign up to set email alerts
|

A Cucumber Necrosis Virus Variant Deficient in Fungal Transmissibility Contains an Altered Coat Protein Shell Domain

Abstract: Little is currently known regarding the specific interactions that govern transmission of plant viruses by their vectors. A cucumber necrosis virus (CNV) variant (LL5) deficient in fungal transmissibility has been isolated from mechanically passaged CNV and characterized. Although LL5 accumulates to wild-type (WT) levels, is capable of rapid systemic infection, and produces stable, highly infectious particles, it is only inefficiently transmitted by Olpidium bornovanus zoospores. The LL5 coat protein (CP) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
45
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 39 publications
6
45
0
Order By: Relevance
“…In cases where plant virus transmission has been studied in detail, the capsid protein has been shown to be the primary determinant for transmission by vectors (13,14,37,40). The interactions between virus capsid proteins and their vectors are either direct or mediated by an accessory or helper protein (22,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where plant virus transmission has been studied in detail, the capsid protein has been shown to be the primary determinant for transmission by vectors (13,14,37,40). The interactions between virus capsid proteins and their vectors are either direct or mediated by an accessory or helper protein (22,38).…”
mentioning
confidence: 99%
“…Genetic studies have revealed that specific viral capsid protein domains and amino acids are determinative for transmissibility and vector specificity. Examples can be found for aphid-transmitted viruses in the genera Potyvirus (1,2,11), Luteovirus (53), Polerovirus (3), Enamovirus (7), and Cucumovirus (35,36,44); for the nematode-transmitted viruses in the genus Tobravirus (25); and for fungus-transmitted viruses in the genera Tombusvirus (18,40) and Benyvirus (52). An emerging theme for a number of these viruses is that a minor capsid protein readthrough protein plays an important role in transmission; this protein is generated by a mechanism involving readthrough of the major capsid protein stop codon (reviewed in reference 4).…”
mentioning
confidence: 99%
“…However, for the most part, the exact role of these amino acids in transmission including their potential role in vector attachment, is not known. Recent work with cucumber necrosis virus (CNV) has suggested that attachment of virions to vector zoospores is an important aspect of the transmission process (24).…”
mentioning
confidence: 99%
“…Transmission of CNV in nature occurs via zoospores of the Chytridiomycete fungus, Olpidium bornovanus (6,9,24). Zoospores and virus particles are released independently into the soil from the roots of infected plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation